Location choices of migrant nest-leavers: Spatial assimilation or continued segregation? - Aslan Zorlu; Clara H. Mulder (Institute for the Study of Labor (IZA), 2010)
We examine ethnic differences in the ethnic composition of the destination neighbourhood upon leaving the parental home using administrative data for the entire birth cohort 1983 living in the Netherlands. The analysis provides little evidence of a clear intergenerational break in the location choices of young men and women from a non-western origin compared to their parents. The neighbourhood choice pattern of those who leave the parental home for independent and shared living arrangements does not differ markedly from that of their parents, while nest-leavers for union formation are more likely to move to neighbourhoods with a relatively small proportion of non-western inhabitants. A decomposition analysis indicates that an overwhelmingly large part of neighbourhood choice is explained by differences in background variables. Particularly, the origin neighbourhood type of nestleavers seems to be a driving force underlying the choice of destination neighbourhood, given individual and parental socioeconomic characteristics.
urn:nbn:de:101:1-201010133354
Keywords: J15; J61; 330; migrants; spatial assimilation; leaving home; Migranten; Jugendliche; Wohnstandort; Soziale Integration; Familiensoziologie; Niederlande